WHAT SMALL BUSINESS NEEDS. - Stans, Maurice H. (The Accounting Review, 1946)
Abstract Today small business binds together many diverse threads of a current problem which is visualized as containing jar-reaching implications, not alone economic but also social and political. Big business is seen as growing ever bigger, more concentrated, and more firmly entrenched, with small business at an ever-increasing disadvantage. The World War is blamed for much of the condition, because the productive power and the know-how in the hands of the larger companies gave them, during that period, an opportunity for tremendous growth and expansion in facilities and permitted them to add materially to their resources. Capital is, of course, essential in some degree to almost any business. In a merchandising venture funds must be available for the purchase of inventories and to finance sales during the period between shipment and collection. The condition of governmental red tape, regulation, and annoyance is a troublesome one for small business. The government of a complex industrial nation like the U.S. must impose controls, limitations, and restrictions on its subjects for the betterment of small businesses in the country.